Penerapan Protokol Kesehatan Covid-19 di Lingkungan Kerja dalam Perspektif Planned Behavioral Theory - Puspa Indah Pratiwi; Siswidiyanto, Siswidiyanto (Jurnal Ilmiah Administrasi Publik, 2023)
The purpose of this study was to determine the application of the Covid-19 health protocol in the work environment based on the Perspective of Planned Behavioral Theory in public organizations in East Java Province, Indonesia. Based on the analysis carried out, the results obtained that a) Attitude has a positive and significant effect on ASN behavior in implementing health protocols in the work environment in the "New Normal" phase; b) Subjective Norms have a positive and significant effect on ASN behavior in the application of health protocols in the work environment in the "New Normal" phase; c) Behavioral control has a positive and significant effect on the behavior of ASN in the application of health protocols in the work environment in the "New Normal" phase; and d) Intention has a positive and significant effect on ASN behavior in the application of health protocols in the work environment in the "New Normal" phase.